Ultrastructure of Giardia duodenalis trophozoites group from hamster: some relevant aspects - Sogayar, Maria Inês L. [UNESP]; Gregório, Elisa Aparecida [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 1991)
Throphozoites of Giardia duodenalis group obtained from fragments or scratched of hamster's mucosa were examined by transission electron microscopy. The fine structure of the trophozoites are presented and comapred with those described for other animals. Some of the trophozoites present the cytoplasm full of glycogen, rough endoplasmic reticulum-like structures and homogeneous inclusions not enclosed by membranes, recognized as lipid drops, which had not been observed in Giardia from other animals. The adhesive disk is composed of a layer of microtubules, from which fibrous ribbons extend into the cytoplasm; these ribbons are linked by layer of crossbridge filaments that shows an intermediary dense band, described for the first time in this paper. The authors regard this band as the result of the cross-bridge filaments slinding in the medium region between adjacent fibrous ribbons, and suggest a contractile activity for them. The role of the adhesive disk on the trophozoite mechanism of attachment to host mucosa is also discussed.
Keywords: Giardia duodenalis; trophozoite; ultrastructure; adhesive disk; hamster